Video-asistovaná tenotomie m. tricipitis surae u pacientů s detskou mozkovou obrnou - Poul, J; Tůma, J; Bajerová, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2005)
PURPOSE OF THE STUDY: The aim of the study was to demonstrate the outcomes of video-assisted tenotomy of the gastrocnemius and soleus muscles in children with the spastic form of cerebral palsy. MATERIAL: In the period from September 2003 to March 2004, 18 lower extremities in 14 patients were operated on.A set for endoscopic plastic surgery with a 4-mm trocar was used. Aponeurotomy was carried out with a scalpel no. 11 or arthroscopic scissors. The treated limb was immobilized in plaster cast for 6 weeks. METHODS The inclusion criteria were: an equinus gait free from a valgus or a varus deviation, preferably unilateral, and the age range between 4 and 10 years. The patients were examined before surgery and followed up at 3-month intervals. RESULTS: In 16 out of 18 treated extremities, simple aponeurotomy of the gastrocnemius and soleus muscles was sufficient to achieve 20 degrees dorsiflexion. In two cases it was necessary to complete the procedure at the same stage by video-assisted sliding double-point tenotomy of the Achilles tendon. The short-term follow-up did not reveal complications such as failure of wound healing or neurological or vascular disturbance. DISCUSSION: The international literature data show that this method has largely been developed on cadavers. Much attention has been given to potential injury to the sural nerve. However, the ultimate goal of this operation, i. e., sufficient correction, should be regarded as a much more important factor. In older children, simple aponeurotomy may not achieve this objective and therefore the authors developed a procedure combining video-assisted aponeurotomy with sliding double-point tenotomy of the Achilles tendon. CONCLUSIONS: Video-assisted tenotomy of the gastrocnemius and soleus muscles proved a fully effective method in our group evaluated at short-term follow-up.
Keywords: šlachy; bérec; endoskopie; Humans; dítě; mozková obrna; Child; Video-Assisted Surgery; lidé; Cerebral Palsy; video-asistovaná chirurgie; Endoscopy; předškolní dítě; kosterní svaly; Tendons; Muscle, Skeletal; Contracture; kontraktura; Child, Preschool; Leg